Preoperative omental metastasis-related maximum standardized fluorine-18-fluorodeoxyglucose uptake value can predict chemosensitivity and recurrence in advanced high-grade serous ovarian cancer patients. Issue 8 (August 2018) - Sun, Yuyun; Liu, Shuai; Feng, Zheng; Cheng, Jingyi; Lu, Linjun; Wang, Mingwei; Yuan, Huiyu; Xu, Junyan; Zhang, Yingjian
Abstract : Objective: The aim of this study was to explore the clinical and prognostic implication of preoperative fluorine-18-fluorodeoxyglucose uptake value of omental metastasis-related in advanced high-grade serous ovarian cancer patients (HGSC). Patients and methods: We retrospectively investigated HGSC patients with omental metastasis (International Federation of Gynecology and Obstetrics stage IIIB–IV) who underwent PET/CT before primary surgery in our hospital between January 2010 and January 2016. All patients were confirmed omental metastasis by postoperative pathology. None of these patients received neoadjuvant chemotherapy. PET/CT parameters, including maximum standardized uptake value of primary ovary tumor (SUVp), omental metastasis (SUVo), and omental metastasis-to-primary tumor (SUVo/p) were measured. The relationships between PET/CT parameters and clinical characteristics were analyzed by t -test. Kaplan–Meier methods and log-rank tests were used to analyze progression-free survival (PFS) in univariate analysis. For multivariate analysis, COX regression analysis was used to assess the prognostic predictive value of PET/CT-derived variables. Results: Totally 81 advanced HGSC patients with omental metastasis were enrolled in our study, and 49 (60.5%) patients experienced recurrence and disease progression. The median (range) follow-up time was 18.5 (7–72) months. Older patients showed higher level of SUVo/p ( P =0.006). Chemosensitive patients had lower levels of SUVo ( P =0.009) and SUVo/p ( P <0.001) than those chemoresistant ones. In univariate analysis, patients with better PFS were associated with lower SUVo ( P <0.001) and SUVo/p ( P <0.001). Multivariate analysis found only SUVo/p was an independent factor for PFS ( P =0.006). Conclusion: Preoperative SUVo/p measured by fluorine-18-fluorodeoxyglucose PET/CT appeared to be an independent predictive factor for recurrence in advanced HGSC patients. Chemosensitive patients had lower omentum-related SUV values than those chemoresistant ones.